صورة المجتمع الجزائري في رواية سلالم ترولار مقاربة في ضوء النقد الثقافي - الزاوي، سليم; مومني، عبد العالي; فار، يوسف (University of Eloued جامعة الوادي, 2025)
يعد النقد الثقافي من أهـم الظواهر الأدبية ما بعد الحداثـة في الأدب والنقد، اذ يهتـم بكشف الأنساق المضمرة في النصوص الأدبية ودراستها، واعطاء صورة حقيقية للواقع المعاش. فتهدف دراستنا الموسومة بـ<< صورة المجتمع الجزائري في رواية سلالم ترولار لسمير قسيمي – مقاربة في ضوء النقـد الثقافـــــي >> إلــى الكشـف عن هذه الأنساق في الروايـــــة و تحديد دلالتها الثقافية من خلال بنية الشخصية، كما أن الرواية حافلة بمجموعة من الأنساق الثقافية ركزنا على بعض منها فيما يخدم دراستنا، التي كانت عبارة عن مدخل تمهيدي للموضوع و فصلين أولهما تطرق إلى الجذور النظرية للنقد الثقافي و مفهوم شبكة الأنساق الثقافية أما الفصل الأخير فقد فاتسم بالعملية التحليلية التفكيكية التطبيقية للكشف عن الدلالات الثقافية لشخصيات الرواية، وكذا الأنساق الثقافية المضمرة التي أراد سمير قسيمي ايصالها لجمهوره، بأسلوب فنتازي تهكمي ساخر، ثم خاتمة والتي تضمنت أهم نتائج الدراسة. Cultural criticism is one of the most important postmodern literary phenomena in literature and criticism, as it is concerned with revealing and studying the implicit patterns in literary texts, and providing a true picture of lived reality. Our study, entitled “The Image of Algerian Society in Samir Kasimi’s Novel The Stairs of Trolar - An Approach in the Light of Cultural Criticism,” aims to reveal these patterns in the novel and determine their cultural significance through the character structure. The novel is also full of a group of cultural systems, some of which we have focused on in order to serve our study, which was an introductory introduction to the subject and two chapters, the first of which addressed the theoretical roots of cultural criticism and the concept of the network of cultural systems, while the last chapter was characterized by the analytical deconstructive application process to reveal the cultural connotations of the characters of the novel. And also the hidden cultural patterns that Samir Qasimi wanted to convey to his audience, in a sarcastic, satirical, and fantasy style, then a conclusion that included the most important results of the study
مذكرة ماستر. نقد حديث ومعاصر.2025